Diversion for Juvenile Offenders Involved in Gang-Related Crimes - Isnaeni Abdillah Liat Mauli; Ifahda Pratama Hapsari (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2025)
This study examines the implementation of diversion policies for adolescents involved in gang activities within the juvenile criminal justice system in Indonesia. The phenomenon of children involved in criminal gangs is on the rise, raising legal and social concerns. Diversion of children from formal prosecution is regulated in Law No. 11 of 2012 on SPPA and PERMA No. 4 of 2014. This study employs a normative legal method with a literature review approach, analyzing legislation, legal literature, and court rulings. The findings indicate that although diversion policies are well-regulated in theory, their implementation faces significant challenges, including a lack of understanding among officials, limited facilities, and weak coordination between institutions. As a result, there is an urgent need to strengthen the regulatory framework, enhance the capacity of implementers, and adopt a more contextual and community-based approach to ensure the optimal implementation of diversion strategies.